Differential expression of aromatase, estrogen receptor alpha and 17 beta-HSD associated with the processes of total testicular regression and recrudescence in the bat Myotis nigricans (Chiroptera: Vespertilionidae) - Beguelini, Mateus R. [UNESP]; Falleiros, Luiz R. [UNESP]; Goes, Rejane M. [UNESP]; Rahal, Paula [UNESP]; Morielle-Versute, Eliana [UNESP]; Taboga, Sebastiao R. [UNESP] (Elsevier B.V., 2014)
Despite the worldwide distribution and many unique reproductive adaptations that bats present, many aspects of their reproductive hormonal regulation have not been adequately studied, especially in species that presented patterns of total testicular regression. Thus, this study aimed to evaluate the testicular expression of 17 beta-HSD type 1, aromatase and ER alpha in the bat Myotis nigricans, during the four periods of its reproductive cycle. Immunoreactivity for ER alpha was detected only in the cytoplasm of elongated spermatids and in the nuclei of spermatogonia and Sertoli cells. Expression of aromatase was observed in round and elongated spermatids and in Sertoli and Leydig cells. Immunoreactivity for 17 beta-HSD was restricted to the cytoplasm of Leydig cells. The three expression patterns varied significantly during the four periods of the reproductive cycle. Expression of ER alpha and aromatase in spermatids was continuous, while expression of ER alpha in spermatogonia occurred only in initial types (A(p)). Expression of ERa, and aromatase in Sertoli cells varied, with expression only in periods of spermatogenetic activities; and the same variation was observed for the expression of aromatase and 17 beta-HSD in Leydig cells. We, therefore, propose that the processes of total testicular regression and posterior recrudescence suffered by M. nigricans from September to January in the northwest of the Sao Paulo State of Brazil, are directly regulated by testosterone and estrogen. This occurs via the production of testosterone by 17 beta-HSD, its conversion into estrogen by aromatase, and activation/deactivation of Sertoli cells' AR and spermatogonia's ER alpha. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Estrogen; Hormones; Regulation; Reproduction; Seasonality